2019
DOI: 10.1177/0284185118824782
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TOF-MRA and silent scan-MRA in depicting cerebral arteries in patients with Moyamoya disease

Abstract: Background Silent scan magnetic resonance angiography (silent-MRA) as an arterial spin labeling technique offering sound reduction is insensitive to saturation effect. Time-of-flight (TOF)-MRA has limitations in terms of fine or slow-flow blood vessels due to sensitive saturation effects. Purpose Silent-MRA was compared with TOF-MRA for visualizing cerebral arteries in patients with Moyamoya disease (MMD). Material and Methods Forty-one patients with MMD were scanned with both silent-MRA and TOF-MRA. Silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…The signal‐to‐noise ratio (SNR) and contrast‐to‐noise ratio (CNR) were calculated with the following equations 11,17 : SNR=Vσ CNR=VBσ where V represents the average flow signal intensity in the regions of interest (ROIs), B represents the average signal in the background ROIs, and σ is the standard deviation of the signals in the background ROIs. For the signal intensity measurement, ROIs were placed inside a normal artery or defined background (nonvascular background tissue on the midpoint of line between bilateral C1 segment terminals) on the axial images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal‐to‐noise ratio (SNR) and contrast‐to‐noise ratio (CNR) were calculated with the following equations 11,17 : SNR=Vσ CNR=VBσ where V represents the average flow signal intensity in the regions of interest (ROIs), B represents the average signal in the background ROIs, and σ is the standard deviation of the signals in the background ROIs. For the signal intensity measurement, ROIs were placed inside a normal artery or defined background (nonvascular background tissue on the midpoint of line between bilateral C1 segment terminals) on the axial images.…”
Section: Methodsmentioning
confidence: 99%
“…Among the various ASL‐MRA approaches, zero‐echo‐time (ZTE) MRA can diminish the saturation effect, minimize magnetic susceptibility, and reduce acoustic noise by integrating a continuous ASL (cASL) strategy, ZTE acquisition, and three‐dimensional (3D) radial sampling trajectories 14 . Previous studies have demonstrated the promising superiority of cASL‐ZTE‐MRA over TOF‐MRA in the follow‐up assessment of coiled aneurysms and the diagnosis of intracranial artery diseases 15–20 . However, Holdsworth et al implied that marginal blurring along the vessel walls occurs in cASL‐ZTE‐MRA and might be mistaken for vascular lesions 21 .…”
mentioning
confidence: 99%
“…Katsuki et al (19) use this technique to describe the arteries near the cerebral aneurysm with clip and the peripheral cerebral arteries. In addition, other scholars also employed zTE-MRA for evaluating cerebrovascular disorder in clinic, including cerebral arteriovenous malformation and moyamoya disease (20)(21)(22). In essence, zTE-MRA uses a continuous ASL strategy and a zTE radial acquisition readout scheme (23).…”
Section: Original Articlementioning
confidence: 99%
“…Time-of-flight magnetic resonance angiography (TOF-MRA) is a fast and non-invasive method and used for evaluation of postoperative cerebral vasospasm, but clip-induced artifact limits assessment of the artery in the vicinity of the clip, especially of aneurysm neck remnants. [ 1 ] MRA with ultrashort echo time (UTE-MRA) reduces metal artifact,[ 3 , 7 - 9 ] and its usefulness is reported for the assessment of the internal flow in the intracranial stent,[ 4 , 10 ] moyamoya disease,[ 12 ] and arteriovenous malformation. [ 13 ] Besides, 1.5T UTE-MRA revealed the artery in the vicinity of a clip,[ 5 ] but the obtained image is too rough to evaluate the aneurysm remnant, and its description range is too narrow to assess the cerebral vasospasm especially of the peripheral portion.…”
Section: Image Reportmentioning
confidence: 99%